The Influence of Internal Control Systems, Organizational Justice and Ethical Climate on Human Resource Integrity in the Public Sector - Enny Diah Astuti; Dominica Dini Afiat; Rhina Pongtuluran; Abdul Haris M. Zen; Apriani Riyanti; Fatimah Malini Lubis (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The internal control systems, organizational justice and ethical climate are being investigated as influences on the integrity of human resources in public administration by this study as it were. The study regards that the integrity of public servants is the most important factor in the development of a governance system that is both transparent and accountable. The researchers applied a quantitative explanatory method and surveyed 180 public sector civil servants selected by purposive sampling. For data collection a five-point Likert scale questionnaire was used, and data analysis was by means of multiple linear regression. All three factors: internal control systems, organizational justice and ethical climate were positively and significantly associated with the integrity of human resources. Theoretical aspect of this research will support the public management and organizational behavior literature on civil servant integrity. However, the implications of the research results point to the public agencies' leaders to create the control systems, organizational justice policies and ethical climate that should be strengthened to promote civil servants' integrity and improve public services quality.